2020
DOI: 10.1021/acs.cgd.9b01220
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor-like Behavior and Structure Features of Bi2Ti2O7 Pyrochlore Single Crystals

Abstract: By slow cooling of the melt, large Bi2Ti2O7 single crystals with a composition close to stoichiometric were grown. No traces of impurity phases were found on the X-ray diffraction patterns. A structural model with the space group Fd m and displacive disorder in Bi-sublattice was proposed based on X-ray single crystal diffraction data. The dielectric properties of Bi2Ti2O7 single crystals as a function of temperature at different frequencies were studied for the first time. As in the case of ceramic samples, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
(97 reference statements)
1
16
0
Order By: Relevance
“…The parameters of the relaxation process for the BScTO and BInTO compounds are in good agreement with those for pure BTO, 15 other rare‐earth doped BTO, 21,32,33,35,56 , and bismuth zinc niobate pyrochlores 57–59 . The structural defects are supposed to play a significant role in dielectric relaxation processes 56,60 .…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The parameters of the relaxation process for the BScTO and BInTO compounds are in good agreement with those for pure BTO, 15 other rare‐earth doped BTO, 21,32,33,35,56 , and bismuth zinc niobate pyrochlores 57–59 . The structural defects are supposed to play a significant role in dielectric relaxation processes 56,60 .…”
Section: Resultssupporting
confidence: 69%
“…As shown in Figure 4, a frequency‐dependent maximum of the dielectric constant and dielectric losses is observed for all compositions. This feature of a relaxor‐type dielectric has also been revealed in other bismuth‐based pyrochlores 15,17,20,21,32,33 . For a more detailed analysis of the relaxation process, we applied the formalism of the electrical module 54,55 : M*=M+iM=iωCoZ*, M=ωCoZ, M=ωCoZ,where ( Z ′, M ′) and ( Z ″, M ″) are the real and imaginary parts of the impedance and electrical module, ω = 2π f is the angular frequency, C o is the vacuum capacitance.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Whether Bi 2 Ti 2 O 7 is ferroelectrics is still a controversial issue 43,44 . The dielectric permittivity of Bi 2 Ti 2 O 7 is found to be evidently lower than that of BNT‐BT‐xSNN ceramics 45 . And the ferroelectricity of the non‐stoichiometric pyrochlore Bi 1.74 Ti 2 O 6.624 has never been reported until now.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 The dielectric permittivity of Bi 2 Ti 2 O 7 is found to be evidently lower than that of BNT-BT-xSNN ceramics. 45 And the ferroelectricity of the non-stoichiometric pyrochlore Bi 1.74 Ti 2 O 6.624 has never been reported until now. Therefore, it can be concluded that the secondary phase of Bi 1.74 Ti 2 O 6.624 may lead to the decrease of polarization.…”
Section: Methodsmentioning
confidence: 99%